Retinoic acid modulates peritoneal macrophage function and distribution to enhance antibacterial defense during inflammation - Qin, Yujuan; Wang, Xi; Zhang, Xiamin; Nong, Lianting; Hou, Qiyan; Chen, Yuhong; Li, Yuting; Lin, Wenxian; Mao, Xiuli; Wu, Kezhao; Nong, Wenqian; Wang, Tonghua; et al. (Frontiers in Nutrition, 2025)
BackgroundPeritoneal macrophages, comprising large peritoneal macrophages (LPMs) and small peritoneal macrophages (SPMs), play a vital role in maintaining immune defenses during inflammation. However, the molecular mechanisms governing their responses, particularly the impact of retinoic acid (RA), remain poorly understood. This study aims to elucidate the role of RA in modulating macrophage function, distribution, and immune responses during bacterial infections.MethodsA murine model of peritonitis was established using Escherichia coli expressing a tdTomato fluorescence marker. The effects of RA on macrophage phagocytic capacity, population dynamics, and transcriptomic profiles were assessed using immunofluorescence, flow cytometry, RNA sequencing, and quantitative PCR. Additionally, RA-loaded ZIF-8 nanoparticles were employed to investigate the sustained effects of RA delivery.ResultsRA significantly enhanced macrophage phagocytic activity, delayed functional decline, and promoted the recruitment of SPMs in the peritoneal cavity. Transcriptomic analysis revealed upregulation of leukocyte migration and cell adhesion pathways in RA-treated SPMs. RA treatment also induced distinct gene expression profiles in macrophage subpopulations, reflecting its role in immune modulation. Notably, RA-loaded ZIF-8 nanoparticles prolonged RA retention within macrophages, sustaining its effects.ConclusionRA enhances antibacterial defense by modulating macrophage activity, providing new insights into immune regulation. These findings underscore the therapeutic potential of RA and its nanoparticle formulations in managing bacterial infections and inflammation.